2020
DOI: 10.18332/tid/120077
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic characteristics, paternal smoking and secondhand tobacco smoke exposure among infants in Jakarta, Indonesia

Abstract: INTRODUCTION Prevalence of paternal smoking is high in Asia and babies are vulnerable to secondhand tobacco smoke (SHS) exposure at home. This study assesses socioeconomic characteristics and paternal smoking in households and infants' exposure to SHS. METHODS A cross-sectional analysis of data collected as part of a prospective cohort study was conducted in Jakarta, Indonesia during 2017-2019. Participants were 156 mother-baby pairs whose babies reached the age of 6 months. Socioeconomic characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Based on the Maternal and Child Health Pro le (2020), the number of working mothers or women in urban and rural areas do not have a big difference, namely working mothers have higher health complaints (29.62%) than mothers who do not work (27, 32%) 16 . This is supported by previous research, which explains the type of work level and the level of knowledge of women in Indonesia have a statistical correlation in smoking families, especially in rural areas 14,17 .…”
Section: Introductionsupporting
confidence: 84%
“…Based on the Maternal and Child Health Pro le (2020), the number of working mothers or women in urban and rural areas do not have a big difference, namely working mothers have higher health complaints (29.62%) than mothers who do not work (27, 32%) 16 . This is supported by previous research, which explains the type of work level and the level of knowledge of women in Indonesia have a statistical correlation in smoking families, especially in rural areas 14,17 .…”
Section: Introductionsupporting
confidence: 84%
“…Detailed descriptions of PEER Health Cohort Study are available in the previous publication. 17 Briefly, Participants admitted to 7 community health centers in Jakarta were recruited during 2017 to 2019. To be eligible for the study, infants had to be at 6 months of age, have enough hair for hair sampling analysis, at least 1 parent (mother and/or father) had to be available for an interview for the study and willing to sign an informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics were similar to studies researching on parents in this country and Indonesia. Children living with smoker father and an extended family member who was a smoker were more likely to expose to SHS (21,22). A local study reported in 2011 found that children with such family background were detected with higher level of GM cotinine concentration (0.71 ng/mL) compared to children living in a non-smoking family (0.32 ng/mL) (21).…”
Section: Discussionmentioning
confidence: 99%